Problem Formulation within open-ended problems: looking through the structure, behavior, function (SBF) and novice-expert (NE) frameworks - Wan Salim, Wan Wardatul Amani; Diefes-Dux, Heidi A. (Elsevier BV, 2012)
Problem formulation is integral to successful problem solving. To introduce problem formulation in first-year engineering classrooms, we utilize model-eliciting-activities (MEAs) – a client-driven engineering problems which guide students individually through problem formulation by asking three questions: Q1) “Who is the client?”, Q2) “In one or two sentences, what does the client need?, and Q3) “Describe at least two issues that need to be considered when developing a solution for the client.” The structure-behavior-function and novice-expert frameworks were used to analyse student responses before and after formal instruction on problem formulation was introduced. Student responses showed improvement with formal instruction.